Brainstem evoked response in bus drivers with noise-induced hearing loss - Santos,Adriana Silveira (2009)
Studies carried out by Brainstem Evoked Auditory Potentials (BEAP) in Noise-Induced Hearing Loss (NIHL) workers show different results in relation to neuronal involvement, not involving bus drivers as study object. AIM: to use BEAP in a prospective case/control clinical study to check whether or not there is neural auditory pathway involvement in bus drivers with NIHL. MATERIALS AND METHODS: we selected 50 bus drivers between 27 and 40 years with mild to moderate NIHL, and 20 individuals between 29 and 40 years with normal hearing and without prior history of noise exposure. BEAP tests were carried out and the traces were analyzed. RESULTS: in the NIHL group, the auditory thresholds in 3, 4 and 6 kHz were significantly higher in the left ear. In the NIHL group, potentials PI, PIII and/or PV were not present in a small number of the individuals; we observed a statistically significant increase in PI, PIII and PV absolute latencies, (LIP) LIP I-III interpeak latencies, bilaterally and LIP I-V in the left ear. CONCLUSION: in the NIHL group, besides sensorial injury, changes in BEAP latencies suggest an early functional injury of the first auditory pathway afferent neuron.